Hamiltonicity in Directed Toeplitz Graphs with s1=1 and s3=4 - Shabnam Malik (Computational and Mathematical Methods)
A directed Toeplitz graph Tns1,⋯,sk;t1,⋯,tl with vertices 1, 2, ⋯, n is a directed graph whose adjacency matrix is a Toeplitz matrix. In this paper, we investigate the Hamiltonicity in directed Toeplitz graphs Tns1,⋯,sk;t1,⋯,tl with s1=1 and s3=4.